Gambling and virtual reality: unraveling the illusion of near-misses effect - Quaglieri, Alessandro; Pizzo, Alessandra; Cricenti, Clarissa; Tagliaferri, Ginevra; Frisari, Francesca Valeria; Burrai, Jessica; Mari, Emanuela; Lausi, Giulia; Giannini, Anna Maria; Zivi, Pierpaolo (Frontiers in Psychiatry, 2024)
Studying gambling behavior is a crucial element in reducing the impact of problem gambling. Nevertheless, most current research is carried out in controlled laboratory settings rather than real-life situations, which raises concerns about how applicable the findings are in the broader context. Virtual reality (VR) has proven to be a valuable tool and has been utilized in various experimental scenarios. A limited number of studies have employed VR to investigate gambling behaviors, and few have explored them in an older adolescent context. This study examined the behavioral and physiological effects of gambling behavior, including problem gambling, gaming addiction, and risk-taking decisionmaking in a sample of 36 high-school students aged between 18 to 20 years using an ad-hoc constructed VR scenario designed to simulate a slot-machine platform. The behavioral results highlighted that participants reporting more problem gambling were sensitive to near-misses: i.e., they bet more after near-misses than after losses. This result may reflect the false belief that gamblers, after near-misses, are closer to winning. Physiological data showed that participants exhibited heart rate deceleration during the anticipation of the outcome, which has been suggested to represent a marker of feedback anticipation processing and hyposensitivity to losses. Overall, this study provides evidence for a new VR tool to assess gambling behaviors and new insights into gambling-related behavioral and physiological factors. Implications for the treatment of problem gambling are discussed.